Flateretusjerte pilspisser fra Trøndelag og Nordmøre - en typologisk-kronologisk studie fra senneolitikum til førromersk jernalder - Bakkene, Kristin Mørkeseth (The University of Bergen, 2022)
This thesis examines the bifacial arrowheads that have been found in the two regions of Trøndelag and Nordmøre in Central Norway. The purpose of the study has been to place the arrowheads within a typological and chronological framework based on morphological similarities and differences between them, as well as previous chronological studies of bifacial arrowheads from Southern Norway and Northern Sweden. In addition to establishing the arrowheads’ typology and chronology, the thesis also considers the distribution of the different types of arrowheads and discusses this within the four different topographic regions in my research area. The thesis also considers the geographical distribution of the arrowheads’ raw materials and whether or not it is possible to identify a geographical boundary between the areas where the arrowheads of the different raw materials have been found. A further discussion is developed which focuses on the different types of bifacial arrowheads in a chronological perspective and whether the variation in my material could reflect natural reasons such as the arrowheads having been produced by human groups living in an isolated place, or personal and identity-related style. Further, the thesis examines the distribution pattern of the most numerous types of arrowheads, the raw materials and arrowhead types in connection with possible cultural influences and how the areas lacking finds of bifacial arrowheads could shed light on human activity pattern and economy. The thesis closes with a discussion of the possible uses of the arrowheads, conceptions of style, and in which ways the arrowheads could enable an interpretation of social contact and communication. Arkeologi mastergradsoppgave ARK350 MAHF-ARK